Recombinant influenza virus expressing HIV-1 p24 capsid protein induces mucosal HIV-specific CD8 T-cell responses. Issue 9 (24th February 2016) - Tan, Hyon-Xhi; Gilbertson, Brad P.; Jegaskanda, Sinthujan; Alcantara, Sheilajen; Amarasena, Thakshila; Stambas, John; McAuley, Julie L.; Kent, Stephen J.; De Rose, Robert
Highlights: Heterologous HIV-1 protein expression from influenza viruses as a vaccine strategy. The influenza NS-segment was modified to encode whole HIV-1 p24 capsid gene. Expression of p24 from influenza viruses by heterologous 2A ribosome skip sequences. Prime-boost immunization induced systemic and mucosal HIV-specific CD8 T-cells. HIV-specific CD8 T-cells were induced in the vaginal mucosa by intravaginal boost. Abstract: Influenza viruses are promising mucosal vaccine vectors for HIV but their use has been limited by difficulties in engineering the expression of large amounts of foreign protein. We developed recombinant influenza viruses incorporating the HIV-1 p24 gag capsid into the NS-segment of PR8 (H1N1) and X31 (H3N2) influenza viruses with the use of multiple 2A ribosomal skip sequences. Despite the insertion of a sizable HIV-1 gene into the influenza genome, recombinant viruses were readily rescued to high titers. Intracellular expression of p24 capsid was confirmed by in vitro infection assays. The recombinant influenza viruses were subsequently tested as mucosal vaccines in BALB/c mice. Recombinant viruses were attenuated and safe in immunized mice. Systemic and mucosal HIV-specific CD8 T-cell responses were elicited in mice that were immunized via intranasal route with a prime-boost regimen. Isolated HIV-specific CD8 T-cells displayed polyfunctional cytokine and degranulation profiles. Mice boosted via intravaginal route induced recall responses from the distal lung mucosa and developed heightened HIV-specific CD8 T-cell responses in the vaginal mucosa. These findings demonstrate the potential utility of recombinant influenza viruses as vaccines for mucosal immunity against HIV-1 infection.